Witold Gombrowicz and Philosophy - Sverdiolas , Arūnas (Colloquia, 2020)
The author of the article examines Witold Gombrowicz’s literary texts, diaries, lectures, essays, interviews and letters, as well as memoirs about him, trying to reconstruct the most important philosophical issues that concerned the writer and to describe the nature of his philosophizing. Gombrowicz’s philosophyzing is placed in the very broad context of the Western philosophical thinking tradition. Subsequently, that context is narrowed down to Jean-Paul Sartre’s existentialism which was closest to Gombrowicz and from which he specified his own position by strictly limiting Sartre’s concept of activistic freedom and self-creation and introducing the issue of pain and suffering.Gombrowicz fundamentally modified Edmund Husserl’s phenomenological conception of the transcendental ego, paradoxically identifying it with his own self. The author of the article also draws attention to the philosophy of life, mentioned neither by Gombrowicz nor the authors who researched his philosophy, which is important for understanding the foundations of writer’s thinking. He also analyzes the relationship between philosophical and literary thinking, the personality or even privacy of philosophizing, the “implementation” of philosophical thinking, and other issues.
Keywords: ego; existentialism; phenomenology; philosophy of life; Edmund Husserl; literature; Jean-Paul Sartre